Thigh positioned wearable resistance affects step frequency not step length during 50 m sprint-running - Macadam, P.; Nuell, S.; Cronin, J. B.; Uthoff, A. M.; Nagahara, R.; Neville, J.; Graham, S. P.; Tinwala, F. (European Journal of Sport Science, 2020)
This study determined the acute changes in spatio-temporal and impulse variables when wearable resistance (WR) of 2% body mass was attached distally to the thighs during 50 m maximal sprint-running. Fifteen sub-elite male sprinters performed sprints with and without WR over 50 m of in-ground force platforms in a randomised order. A paired t-test was used to determine statistical differences (p < .05), with effect sizes (ES) calculated between conditions over steps: 1-4, 5-14, and 15-23. WR resulted in small increased 10 and 50 m sprint times (1.0%, ES = 0.31, 0.9%, ES = 0.44, respectively, p > .05) compared to the unloaded sprint condition. For spatio-temporal variables, the WR condition resulted in moderate ES changes in step frequency (-2.8%, ES = -0.53, steps 5-14, p > .05), and contact time (2.5%, ES = 0.57, steps 5-14, and 3.2%, ES = 0.51, average of 23 steps, p > .05), while step length was unaffected during all step phases of the sprint (ES = 0.02-0.07, p > .05). Regarding kinetics, during steps 5-14, WR resulted in a moderate decrease (-4.8%, ES = -0.73, p < .05) in net anterior-posterior impulses and a moderate decrease in vertical stiffness (-5.7%, ES = -0.57, p > .05). For athletes seeking to overload step frequency and develop anterior-posterior impulse during mid to late accelerated sprinting, WR enables the application of a sprint-specific form of resistance training to be completed without decreasing step length.